A mixed-methods study of the demographic and behavioural correlates of walking to a more distant bus stop. (July 2020) - Ragaini, Bruna S.; Sharman, Melanie J.; Lyth, Anna; Jose, Kim A.; Blizzard, Leigh; Peterson, Corey; Johnston, Fay H.; Palmer, Andrew; Aryal, Jagannath; Williams, Julie; Marshall, Elaine A.; Morse, Megan; et al.
Abstract: Walking to more distant public transport stops is commonly promoted for physical activity gain. We examined the uptake of, and reasons for, this behaviour and its correlates through a cross-sectional survey (n = 944) and independent interview study (n = 22). Quantitative analysis examined correlates of frequency of walking to more distant bus stops, including demographic variables, past week bus use, bus stop accessibility, and physical activity. Interviews explored reasons for engaging in this behaviour. Of participants (38%) who had used the bus the previous week, 13% had walked to a more distant bus stop every/most times. Median walking and total physical activity were highest ( P  = 0.003) among this group (210 and 465 min/week, respectively) compared to those who did sometimes (150 and 260 min/week, respectively) or not at all (150 and 270 min/week, respectively). Among interview participants who engaged in this behaviour (n = 12), over half did so for physical activity gain, with the remaining being driven by other co-benefits. Many interviewees overlooked the physical activity benefit of this behaviour. This novel study integrated quantitative and qualitative data and discovered those who walk to more distant public transport stops were generally more physically active than those who do not. While some users were aware of the health benefits, many did so for other reasons. Highlights: Public health messages often promote walking to a further public transport stop. Only a small proportion of bus users regularly engaged in this behaviour. Those who walked to a more distant bus stop frequently were more physically active. The non-health co-benefits of this behaviour may be used in public health messaging.